UPAYA PENGENDALIAN SOSIAL APARATUR GAMPONG TERHADAP PERILAKU MENYIMPANGAN REMAJA DI GAMPONG PAYA DAPUR KABUPATEN ACEH SELATAN - Arba iyah; Irma Juraida (Jurnal Society : Pengamat Perubahan Sosial, 2023)
Deviant behavior is a condition where the behavior of the community is considered not in accordance with the rules, habits, and social norms that exist in the prevailing social life of the community so that it can cause problems. The problem that arises in this study is that deviations are committed by adolescents in a unique location, namely public facilities in the form of bridges connecting villages. In the context of this research aims to describe the social control efforts of the village apparatus in dealing with adolescent deviant behavior. Analysis of this research problem uses qualitative methods with descriptive analysis. From the research that has been made, it is found that the social control efforts that have been made by the Paya Dapur village apparatus are persuasive efforts through reprimands and monitoring, as well as the existence of a warning board in the form of rules that must be obeyed and coercive efforts, namely punishment or sanctions. With the existence of social control and control carried out by the village apparatus, deviations can be minimized.